Rebuilding fish communities: the ghost of fisheries past and the virtue of patience. Issue 2 (1st March 2013) - Collie, Jeremy; Rochet, Marie-Joëlle; Bell, Richard
Abstract : The ecosystem approach to management requires the status of individual species to be considered in a community context. We conducted a comparative ecosystem analysis of the Georges Bank and North Sea fish communities to determine the extent to which biological diversity is restored when fishing pressure is reduced. First, fishing mortality estimates were combined to quantify the community‐level intensity and selectivity of fishing pressure. Second, standardized bottom‐trawl survey data were used to investigate the temporal trends in community metrics. Third, a size‐based, multispecies model (LeMans) was simulated to test the response of community metrics to both hypothetical and observed changes in fishing pressure in the two communities. These temperate North Atlantic fish communities have much in common, including a history of overfishing. In recent decades fishing pressure has been reduced, and some species have started to rebuild. The Georges Bank fishery has been more selective, and fishing pressure was reduced sooner. The two communities have similar levels of size diversity and biomass per unit area, but fundamentally different community structure. The North Sea is dominated by smaller species and has lower evenness than Georges Bank. These fundamental differences in community structure are not explained by recent fishing patterns. The multispecies model was able to predict the observed changes in community metrics better on Georges Bank, where rebuilding is more apparent than in the North Sea. Model simulations predicted hysteresis in rebuilding community metrics toward their unfished levels, particularly in the North Sea. Species in the community rebuild at different rates, with smaller prey species outpacing their large predators and overshooting their pre‐exploitation abundances. This indirect effect of predator release delays the rebuilding of community structure and biodiversity. Therefore community rebuilding is not just the sum of single‐species rebuilding plans. Management strategies that account for interspecific interactions will be needed to restore biodiversity and community structure.